PEMBERDAYAAN SANTRI PONDOK PESANTREN AL MUBARAK SUDIANG DALAM PEMBUDIDAYAAN DAN PEMANFAATAN TANAMAN OBAT - Ratnasari Dewi; Mudyawati Kamaruddin; Hendra Stevani; Muli Sukmawaty; Ivonne Siswanty; Rafidah Rafidah (Community Development Journal, 2022)
Based on interviews with a partner, the following community partner issues were lack of medicinal plants gardens around the Al Mubarak Sudiang Islamic boarding school, lack of knowledge and introduction to the types of plants with medicinal properties, and lack of knowledge about the health benefits of medicinal plants. Using traditional medicinal plants is the community's active participation in solving health problems. The community service partner were students in Al Mubarak boarding school. The solution to overcome the partner's problems was empowerment with a participatory learning approach emphasizing learning through consultation, training, coaching, and demonstration/simulation of medicinal plant cultivation and utilization. Then, the authors evaluated program implementation and sustainability before and after activities. The evaluation showed increased achievement levels in all success indicators. Thus, this community service had significant benefits for all participants. In conclusion, the empowerment of students in Al Mubarak Sudiang Islamic Boarding School can increase their knowledge in medicinal plants cultivation and utilization, skills in medicinal plants cultivation, and medicinal plants utilization. The local government should support and participate in the sustainability of this community service through small industries producing healthy drinks from medicinal plants.